Detection of volatile organic compounds associated with mechanical damage in apple cv. 'Golden Delicious' by headspace solid-phase microextraction (HS-SPME) and GC-MS analysis. (30th December 2022) - Martínez, Ana; Hernández, Alejandro; Moraga, Carlos; Tejero, Paula; Córdoba, María de Guía; Martín, Alberto
Abstract: The aim of this study was to investigate changes in the volatile organic compound (VOC) profile of apples cv. 'Golden Delicious' associated with mechanical damage. The performance of direct and indirect extraction methods and four solid-phase microextraction (SPME) fibres coated with different stationary phases (CAR/PDMS, PDMS, DVB/CAR/PDMS, and CW/TPR) was tested for identifying volatile markers of damaged and sound fruit. Direct extraction and CAR/PDMS fibre were proposed for the extraction of VOCs associated with mechanical damage in apples. Almost half of the 83 compounds extracted were identified as esters (41 different VOCs), followed by hydrocarbons (11), alcohols (10), and terpenoids (7), among others. The more evident changes were an increase of lower molecular weight esters such as methyl, ethyl, and propyl acetate; and a decrease of other higher molecular weight esters such as phenyl ethyl acetate, isobutyl butyrate, and butyl butanoate. The ester ratios suggest that the relation between ethyl acetate and phenyl ethyl acetate is the best option for detecting mechanical damage in cv. 'Golden Delicious' apples. Highlights: VOC profiles of apples associated with mechanical damage were studied. Performance of extraction methods and four SPME fibres was investigated. Direct extraction with CAR/PDMS fibre was proposed for determining VOC markers. Low molecular weight acetate esters were identified as VOC damage markers. Ethyl acetate: phenyl ethyl acetate ratio is proposed as a marker of apple damage.